Pola Asuh Orang Tua dalam Pendidikan Anak di Keluarga - Evryeni Jusmadi; Naini Niken Navita; Nadinda Cleo Vatra; Meyza Yolanda Putri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This article aims to examine parenting styles in children’s education within the family from a theoretical perspective while also describing field findings through an interview with a parent. The family is the first and primary educational environment that plays a crucial role in shaping a child’s character, personality, and social behavior. Authoritarian and permissive parenting styles tend to hinder a child’s social and emotional development. The results of the interview with the informant (Mrs. Yuni Indarsih, 42 years old, a homemaker) indicate that an authoritarian parenting style is consistently applied based on the belief that firmness fosters discipline and a child’s success. The primary challenges faced include the influence of peer groups and excessive gadget use. The conclusion of this article emphasizes that a warm, responsive, consistent, and role-model-based parenting style is the key to optimal character development in children.